2023
DOI: 10.1136/bmjopen-2022-069877
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an oral health curriculum in reducing dental caries increment and improving oral hygiene behaviour among schoolchildren of Ernakulam district in Kerala, India: study protocol for a cluster randomised trial

Abstract: IntroductionChildren’s learning abilities suffer when their oral health is compromised. Inadequate oral health can harm children’s quality of life, academic performance, and future success and achievements. Oral health problems may result in appetite loss, depression, increased inattentiveness, and distractibility from play and schoolwork, all of which can lower self-esteem and contribute to academic failure. An oral health curriculum, in addition to the standard school curriculum, may instil preventive oral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Most failed to show a significant reduction in caries unless combined with fluoride mouth rinses and application of topical fluorides. 52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most failed to show a significant reduction in caries unless combined with fluoride mouth rinses and application of topical fluorides. 52…”
Section: Discussionmentioning
confidence: 99%
“…Most failed to show a significant reduction in caries unless combined with fluoride mouth rinses and application of topical fluorides. 52 At an individual level, tooth brushing with fluoride toothpaste has shown standalone benefit in reducing caries prevalence, while other strategies, such as the application of fluoride varnish, do not appear effective in isolation to reduce caries progression. 53 A Cochrane systematic review evaluating the impact of tooth brushing showed a 24% reduction in caries experience as measured by DFMS scores among children using fluoridated toothpaste versus those using non-fluoridated toothpaste.…”
Section: Discussionmentioning
confidence: 99%